De migraciones, sociologías e imaginarios - Santamaría Lorenzo, Enrique (Sociedad y Economía, 2005)
This paper deals with the symbolic dimensión of migrations, in particular with the "symbolic work" that the different social actors perform, with their practices and representations, upon the current migratory phenomena, making of the immigrant a more and more central character of the social imagining. In this way we intend to examine the way in which we think and imagine the immigration (the immigrants) to Spain. Being aware that there is no complete impermeability between social imagining and science, on the contrary, that there is a continuous feedback between them, we cali, on the one hand, upon a permanent exercise of "epistemological vigilance" in order to have in mind the social génesis, scope and use of terms, concepts and theories we use in our research tasks and, on the other hand, upon the sociological imagination in order to induce alternative forms of thought (and action) within the heterogeneous and complex socio-cultural dynamics of the current transnational migrations.